CD23 and CD6 molecule expression in chronic lymphoid leukemia (CLL) pateints - Baydaa Hameed Abdullah; Haethem Qassim Mohammed; Talib M. Hussein (Iraqi Journal of Cancer and Medical Genetics, 2011)
This study has been conducted on blood samples from patients with chronic lymphoid leukemia’s (CLL) who were diagnosed and treated at The National Center of Hematology between January 2006 to September 2009.The diagnosis was established depending on clinical and hematological findings. Immunophenotyping was performed by indirect immunofluorescence technique using fluorescent microscopy to identify CD 23 and CD 6 markers expression on peripheral blood mononuclear cells. Positive cell is seen with multiple fluorescence dyes around the membrane or by bright green membrane fluorescence, the cases considered as positive for marker when the marker is expressed in ≤ 30 of cells.Sixty cases were newly diagnosed untreated CLL patients with mean age of 64.5 ± 10.1 years with 9.4% of cases below the age of 45 years and male to female ration of 3:1were involved in this study.Immunological study showed that all the cases were CD 23 positive while CD6 were positive in 45 (75%) out of 60 cases and negative in 15(25%) out of 60 cases. These percentages in all CD 23 positive cases and CD6 positive CLL patients were higher significant than normal group (p=0.000).In conclusion, the positive CD23 expression clarify that the majority of chronic lymphoid leukemia are B-cell type .B-cell is the most common which is heterogeneous disease regarding clinical presentation ,hematological findings and morphological feature although CD6 is not specific marker for diagnosis of CLL ,but it may help in the diagnosis of CLL.